Spending behavior under budget constraint: An integrated model of cognitive, regulatory, and social determinants among need-based scholarship students in Indonesia - Widi Setiawan; Rasyidi Faiz Akbar (Jurnal Ilmu Manajemen, 2026)
This study examines the determinants of spending behavior among recipients of the Kartu Indonesia Pintar Kuliah (KIP-K), a need-based scholarship program in Indonesia. While financial aid programs are designed to improve access to higher education, limited attention has been given to how students allocate financial assistance under conditions of budget constraint. Drawing on the Theory of Planned Behavior (TPB), this study develops an integrated model that incorporates cognitive (financial literacy), self-regulatory (delayed gratification), and social (peer influence and lifestyle) determinants to explain students' spending behavior. A quantitative cross-sectional survey was conducted involving 394 active KIP-K recipients from various universities in Indonesia. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that financial literacy and delayed gratification positively and significantly influence responsible spending behavior, with delayed gratification emerging as the strongest predictor. In contrast, peer influence and lifestyle do not significantly affect spending behavior. The model explains a substantial proportion of the variance in students' spending behavior, indicating moderate predictive power. These findings suggest that internal self-regulatory capacity plays a more dominant role than social pressures or lifestyle preferences in shaping financial decisions among students facing financial constraints. This study contributes to the literature by repositioning spending behavior as a resource allocation behavior under budget constraints and by extending the Theory of Planned Behavior to the context of need-based scholarship recipients. The findings also provide policy implications for improving the effectiveness of student financial aid programs through financial literacy and self-regulation interventions.